Pragmatic intervention for increasing self-directed exercise behaviour and improving important health outcomes in people with multiple sclerosis: a randomised controlled trial. (July 2014) - Carter, A; Daley, A; Humphreys, L; Snowdon, N; Woodroofe, N; Petty, J; Roalfe, A; Tosh, J; Sharrack, B; Saxton, JM
Background: Exercise programmes that can demonstrate evidence of long-lasting clinical effectiveness are needed for people with multiple sclerosis (P w MS). Objective: The objective of this study was to assess the effects of a practically implemented exercise programme on self-directed exercise behaviour and important health outcomes in P w MS to nine months of follow-up. Methods: We conducted a parallel-arm, randomised controlled trial: 120 P w MS (Expanded Disability Status Scale (EDSS) 1.0–6.5) randomised to a three-month exercise intervention plus usual care, or usual care only. Two supervised plus one home-exercise session (weeks 1–6) were followed by one supervised and two home-exercise sessions (weeks 7–12). Cognitive-behavioural techniques promoted long-term exercise behaviour change. Outcomes were blindly assessed at baseline and at three and nine months after randomisation. The primary outcome was self-reported exercise behaviour (Godin Leisure Time Exercise Questionnaire (GLTEQ)). Secondary outcomes included fatigue and health-related quality of life (HRQoL). Results: The intervention increased self-reported exercise (9.6 points; 95% CI: 2.0 to 17.3 points; p = 0.01) and improved fatigue ( p < 0.0001) and many HRQoL domains ( p ≤ 0.03) at three months. The improvements in emotional well-being ( p = 0.01), social function ( p = 0.004) and overall quality of life ( p = 0.001) were sustained for nine months. Conclusion: This pragmatic approach to implementing exercise increases self-reported exercise behaviour, improves fatigue and leads to a sustained enhancement of HRQoL domains in P w MS.